2016
DOI: 10.4103/0973-029x.190951
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase-9 in oral potentially malignant disorders: A systematic review

Abstract: Matrix metalloproteinase-9 (MMP-9) is an inducible enzyme. Oral potentially malignant disorders (OPMDs) are considered as the early tissue changes that happen due to various habits such as smoking tobacco, chewing tobacco or stress. This alteration in the tissues alters the expression of MMP-9. The rationale of the review is to know the expression of MMP-9 in OPMDs. Hand searching and electronic databases such as PubMed and ScienceDirect were done for mesh terms such as OPMDs and MMP-9. Eight articles were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…MMPs can degrade the extracellular matrix. It is secreted by neutrophils, macrophages, and fibroblasts, on the stimulus provided by transforming growth factor β and interleukin-8 (Venugopal and Uma Maheswari, 2016). The MMP sustains the bioavailability of growth factors, thus aiding in the proliferation of cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMPs can degrade the extracellular matrix. It is secreted by neutrophils, macrophages, and fibroblasts, on the stimulus provided by transforming growth factor β and interleukin-8 (Venugopal and Uma Maheswari, 2016). The MMP sustains the bioavailability of growth factors, thus aiding in the proliferation of cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs can be classified as gelatinases, collagenases, stromelysins, and membrane-type MMPs (Wu et al, 2010;Hema Shree et al, 2019) due to their working mechanism which can lead to fragmentation of the FAS receptors, reduction of natural killer cells, and preventing apoptosis. They can have dual role in angiogenesis, increase the bioavailability of vascular endothelial growth factor receptor (VEGFR) (Venugopal and Uma Maheswari, 2016), active role in the cell-to-cell adhesion, cell-to-extracellular matrix adhesion, breakdown of collagen (type IV, V, VII, X), fibronectin and elastin, (Chen et al, 2008) disintegrate several proteins, chemokines, cytokines, and alter their receptors to regulate cell growth and inflammation (Henriques et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review, MMP-9 levels were reported to be elevated in the tissue, serum, and saliva samples of PPOELs compared with controls. 96 However, the limited number of studies did not provide conclusive evidence regarding MMP-9 as a potential marker of MT risk in PPOELs. Besides, it has been proposed that MMP-9 may exhibit diverse oncogenic or tumor suppressive functions under different conditions, related to patient or tumor characteristics.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…Matrix metallo-proteinases (MMPs) a group of enzymes secreted by macrophages, neutrophils and fibroblasts in response to the stimulus from TGF-β and IL-8 and are responsible for the degradation of most extracellular matrix proteins during organogenesis, growth and normal tissue turnover. The secreted MMPs maintain the growth factors bioavailable which results in cancer proliferation (20) . Among many factors included in etiopathogenesis of potentially malignant disorders as leukoplakia, MMP-9 plays a main role in tumorigenesis ranging from initiation/promotion to angiogenesis, dissemination, immunological surveillance and metastatic growth.…”
Section: Introductionmentioning
confidence: 99%